Effects of Organic Pesticides on Enchytraeids (Oligochaeta) in Agroecosystems: Laboratory and Higher-Tier Tests - Römbke, Jörg; Schmelz, Rüdiger M.; Pélosi, Céline (Frontiers in Environmental Science, 2017)
Enchytraeidae (Oligochaeta, Annelida) are often considered to be typical forestliving organisms, but they are regularly found in agroecosystems of the temperate regions of the world. Although less known than their larger relatives, the earthworms, these saprophagous organisms play similar roles in agricultural soils (but at a smaller scale), e.g., influencing soil structure and organic matter dynamics via microbial communities, and having a central place in soil food webs. Their diversity is rarely studied or often underestimated due to difficulties in distinguishing the species. New genetic techniques reveal that even in anthropogenically highly influenced soils, more than ten species per site can be found. Because of their close contact with the soil pore water, a high ingestion rate and a thin cuticle, they often react very sensitively to a broad range of pesticides. Firstly we provide a short overview of the diversity and abundance of enchytraeid communities in agroecosystems. Afterwards, we explore the available data on enchytraeid sensitivity towards pesticides at different levels of biological organization, focusing on pesticides used in (mainly) European agroecosystems. Starting with non-standardized studies on the effects of pesticides on the sub-individual level, we compile the results of standard laboratory tests performed following OECD and ISO guidelines as well as those of higher-tier studies (i.e., semi-field and field tests). The number of comparable test data is still limited, because tests with enchytraeids are not a regulatory requirement in the European Union. While focusing on the effects of pesticides, attention is also given to their interactions with environmental stressors (e.g., climate change). In conclusion, we recommend to increase the use of enchytraeids in pesticide risk assessment because of their diversity and functional importance as well as their increasingly simplified use in (mostly standardized) tests at all levels of biological organization.